2015
DOI: 10.1386/jammr.8.2.83_1
|View full text |Cite
|
Sign up to set email alerts
|

Visible and invisible: An audience study of Muslim and non-Muslim reactions to orientalist representations in I Dream of Jeannie

Abstract: Most Muslims lay the blame for the perpetuation of societal prejudice against Islam and Muslims at the feet of the media. Media scholars regularly confirm that negative stereotypes prevail in contemporary western media. Yet there are differences between media representation and the effects on actual people’s attitudes. Empirical research is needed to find out if negative media stereotypes of Muslims, Arabs and Islam are actually linked to widespread societal Islamophobia. This article traces audience reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The instinctive feeling is that this negative representation accumulates in the minds of many non-Muslim media consumers and is causally connected to anti-Muslim racism. These hypotheses are explored and confirmed with audience reception studies with caveats that viewers with exposure to differentiated news, critical theory, orientalism, or Muslim friends are less likely to adopt hegemonic meanings (Bullock 2015(Bullock , 2017Hall 1980;Rane et al 2014: 36;Saleem et al 2017).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…The instinctive feeling is that this negative representation accumulates in the minds of many non-Muslim media consumers and is causally connected to anti-Muslim racism. These hypotheses are explored and confirmed with audience reception studies with caveats that viewers with exposure to differentiated news, critical theory, orientalism, or Muslim friends are less likely to adopt hegemonic meanings (Bullock 2015(Bullock , 2017Hall 1980;Rane et al 2014: 36;Saleem et al 2017).…”
mentioning
confidence: 75%
“…Typically, due to its emphasis on diversion and amusement, entertainment is often overlooked as a significant source of meaning making -especially by audiences -although it as equally constructed as news to reflect socially and politically dominant ideologies (Park, Gabbadon, and Chernin 2006;Mirrlees 2016). And while it would be nice to contribute to the meagre number of studies tackling causal connections between anti-Muslim racism and watching film and television representations of Islam and Muslims (Bullock 2015;Bullock 2017), this paper is not an audience reception study. I am focused on an analysis of the representation of the veil and turban-veil.…”
Section: Cassmentioning
confidence: 99%
“…13. An audience study of 14 interviewees (seven Muslim women, six non-Muslim women, and one non-Muslim man) found that the non-Muslim viewers did not notice the Orientalist features in the show, while the Muslims were offended by the representation (Bullock 2015). 14.…”
Section: Discussionmentioning
confidence: 99%
“…This latter point highlights a particularly disquieting aspect of Arab-Muslim identity in Western society: if anti-Arab and anti-Muslim racism is to be addressed, the media's role in perpetuating hostile ideologies about their identities needs to change, but if media personnel, critics, and viewers cannot see the racism in the ReOrient 4.1 Produced and distributed by Pluto Journals representation, change will be slow or nonexistent. Arab-Muslim viewers will continue to feel offended by media representation of their communities, and the gulf that separates these communities will be difficult to bridge (Massey and Tatla 2012;Rane, Ewart, and Martinkus 2014;Bullock 2015). As Hall (2007: 487) maintains, cultural studies "has to analyze certain things about the constitutive and political nature of representation itself, about its complexities, about the effects of language, about textuality as a site of life and death.…”
Section: Orientalist Comedy In I Dream Of Jeanniementioning
confidence: 99%